PRODUKTIVITAS KERJA KARYAWAN PADA BPR DI BALI: KAJIAN BERDASARKAN LINGKUNGAN KERJA, DISIPLIN KERJA, DAN KEPUASAN KERJA - I Dewa Made Arik Permana Putra; I Kadek Bagiana; Ida Ayu Nyoman Yuliastuti (Program Studi Manajemen Fakultas Ekonomi dan Bisnis Universitas Mahasaraswati Denpasar, 2024)
This research aims to examine and analyze the influence of the work environment, work discipline and job satisfaction on employee productivity. This research was conducted at BPR in Bali with a research sample of268 respondents taken using saturated sampling techniques. All data obtained from the questionnaire distribution is suitable for use, then analyzed using multiple linear regression, hypothesis testing (t test and f test). The research results show that (1) the work environment has a positive and significant effect on employee productivity at BPR in Bali, so that the better the work environment, the more employee productivity at PT will increase. BPR in Bali (2) Work Discipline has a positive and significant effect on Employee Productivity at BPR in Bali so that the more work discipline increases, the more employee productivity at BPR in Bali (3) Job Satisfaction has a positive and significant effect on Employee Productivity at BPR in Bali, so that the more job satisfaction increases, the more employee productivity at BPR in Bali.